2016
DOI: 10.1136/annrheumdis-2016-eular.4056
|View full text |Cite
|
Sign up to set email alerts
|

FRI0495 The Combined Prevalence of Rare Diseases in Rheumatology Demonstrates A Sum More than Double To That of Ankylosing Spondylitis

Abstract: BackgroundRare diseases (RD) in rheumatology are heterogeneous and thus lack a systemic classification. By definition, prevalences of RD range up to 5/10 000 in Europe. Clinical courses comprise a vast variety of musculoskeletal symptoms such as arthritis, myositis, vasculitis, autoimmune organ involvement and bone diseases. The impact of RD for health care systems is widely unknown and individual patients are prone to unsatisfactory diagnoses and/or treatments.ObjectivesThe objective of this study was to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Studies with less than 10 participants per study arm in the final analysis were excluded. We considered only rheumatic and musculoskeletal diseases as defined by EULAR and the Orphanet classification of rare rheumatic diseases as ORPHA: 182231 (compare Leyens et al [ 1 ] and Orphanet).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies with less than 10 participants per study arm in the final analysis were excluded. We considered only rheumatic and musculoskeletal diseases as defined by EULAR and the Orphanet classification of rare rheumatic diseases as ORPHA: 182231 (compare Leyens et al [ 1 ] and Orphanet).…”
Section: Methodsmentioning
confidence: 99%
“…Rare diseases (RDs) in rheumatology present a heterogeneous group of diverse syndromes, and differ in their etiology, clinical symptoms, prognosis, and outcome in clinical trials. Recently, we identified a set of various RDs in rheumatology [ 1 ], and found that they are highly prevalent when considered as a group. Most of these diseases and syndromes have a prevalence of less than one individual in 100,000, and all of them fall under the European Commission’s definition that specifies RDs as “Any disease affecting fewer than five people in 10,000” [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation